Global, regional and country-level 90–90–90 estimates for 2018: assessing progress towards the 2020 target. (15th December 2019) - Marsh, Kimberly; Eaton, Jeffrey W.; Mahy, Mary; Sabin, Keith; Autenrieth, Christine S.; Wanyeki, Ian; Daher, Juliana; Ghys, Peter D.
Abstract : Background: In 2014, the Joint United Nations Programme on HIV/AIDS (UNAIDS) and partners set the 90–90–90 target for the year 2020: diagnose 90% of all people living with HIV (PLHIV); treat 90% of people who know their status; and suppress the virus in 90% of people on treatment. In 2015, countries began reporting to UNAIDS on progress against 90–90–90 using standard definitions and methods. Methods: We used data submitted to UNAIDS from 170 countries to assess country-specific progress towards 90–90–90 through 2018. To assess global and regional progress, overall and by sex for adults aged 15 years and older, we combined country-reported data with estimates generated with a Bayesian hierarchical model. Results: A total of 60 countries reported on all three 90s in 2018, up from 23 in 2015. Among all PLHIV worldwide, 79% (67–92%) knew their HIV status. Of these, 78% (69–82%) were accessing treatment and 86% (72–92%) of people accessing treatment had suppressed viral loads. Of the 37.9 million (32.7–44.0 million) PLHIV worldwide, 53% (43–63%) had suppressed viral loads. The gap to fully achieving 73% of PLHIV with suppressed viral load was 7.7 million; 15 countries had already achieved this target by 2018. Conclusion: Increased data availability has led to improved measures of country and global progress towards the 90–90–90 target. Although gains in access to testing and treatment continue, many countries and regions are unlikely to reach the 90–90–90 target by 2020. Abstract : Supplemental Digital Content is available in the text